Kecekapan pembelajaran berasaskan model contoh-masalah dalam pembelajaran teori litar - Jalani, Noor Hisham (2015)
The purpose of this study was to develop and test the effectiveness of Example-Problem-Based Learning (EPBL) teaching model on the student's knowledge acquisition, learning transfer, and mental effort. The effects of these variables on the learning efficiency are also explored. An experiment with pre-test and post-test design was carried out on students of the Diploma in Mechatronics Technology (DEM) program, who attended the Circuit Theory course (DEM1313) in their first semester in ADTEC. The students were randomly selected and distributed into two groups using two stage cluster sampling. EPBL teaching methods have been implemented to the treatment group (n = 19) for eight weeks, whereas the existing traditional teaching method based on Direct Instruction (DI) is maintained for the control group (n = 19) to compare the validity of the findings. The students have completed three types of instruments: Knowledge Acquisition test, Learning Transfer test, and nine-point scale of Mental Effort. The data were analyzed using MANCOVA and independent sample t-test procedures. Results show that students’ knowledge acquisition [F (1,38) = 4.55, p < 0.05] and learning transfer [F (1,38) = 18.37, p < 0.05] in the EPBL group was significantly higher than students in the control group. Although the mental effort during knowledge acquisition test for the students in both groups did not differ, the mental effort in the EPBL group during the learning transfer test [F (1,38) = 13.87, p < 0.05] and learning phase [t (36) = -4.20, p < 0.05] are lower than the control group. The EPBL group also recorded a positive learning efficiency [t (36) = 4.33, p < 0.05] compared to the control group. Therefore, it can be concluded that the EPBL teaching method enhances students’ knowledge acquisitions, learning transfer, and reducing mental effort during learning transfer test and learning phase; as well as increasing the learning efficiency.